2020
DOI: 10.3390/ijerph17197213
|View full text |Cite
|
Sign up to set email alerts
|

How the Health Rumor Misleads People’s Perception in a Public Health Emergency: Lessons from a Purchase Craze during the COVID-19 Outbreak in China

Abstract: Health rumors often mislead people and cause adverse health behaviors. Especially during a public health emergency, health rumors may result in severe consequences for people’s health and risk governance. Insight into how these rumors form and harm people’s health behavior is critical for assisting people in establishing scientific health cognition and to enhance public health emergency responses. Using the case study with interview data of a salient purchase craze led by a health rumor during the COVID-19 out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 62 publications
1
44
0
6
Order By: Relevance
“…Honest public policy for information disclosure. Complete information disclosure about the risk can determine the level of emergency preparedness and response [ 73 ]. In view of Wuhan’s experience in China, insufficient information disclosure, to an extent, delayed the process of risk management, and resulted in more losses, including deaths and financial/economic losses [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Honest public policy for information disclosure. Complete information disclosure about the risk can determine the level of emergency preparedness and response [ 73 ]. In view of Wuhan’s experience in China, insufficient information disclosure, to an extent, delayed the process of risk management, and resulted in more losses, including deaths and financial/economic losses [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the dissemination process, this message was leveled and sharpened by social media and the public, which jointly formed its falsity. 23 In this case, it is difficult to judge whether this message was shared accidentally or deliberately. Perhaps social media users shared this message with the intention of earning the public’s attention, clicks, or followers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The public with low health literacy not only trust a piece of misinformation readily, but also misunderstand an accurate information and turn the information into a piece of misinformation. 23 Besides, previous research indicated that cultural and social factors profoundly influence health-related behavior as well. 23 For instance, Chinese people have a stubborn belief about TCM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…How could it not be because the virus that is currently hitting, works and attacks humans very quickly? Including building cognitive scientific knowledge related to disease so that there is no mistake about the disease that is currently plaguing and psychological uncertainty where a person is faced with uncertain conditions as happened China [7]. This means that the psychological conditions of the community are very diverse.…”
Section: Literature Reviewmentioning
confidence: 99%